The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/lt.21663
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlation between spleen volume and thrombocytopenia in liver transplant patients: A concept for predicting persistent thrombocytopenia

Abstract: Interferon (IFN) therapy with or without ribavirin treatment is well established as a standard antiviral treatment for hepatitis C virus (HCV)-infected patients. However, susceptibility to thrombocytopenia is a major obstacle for initiating or continuing this therapy, particularly in liver transplant (LTx) recipients with HCV. Studies have reported that splenectomy performed concurrently with LTx is a feasible strategy for conditioning patients for anti-HCV IFN therapy. However, the relationship between the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Recently, Ohira, et.al. reported fine and detailed investigation of the correlations between spleen volume and all three hematological parameters, though even this report investigated up to 6 months after liver transplantation (Ohira et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…Recently, Ohira, et.al. reported fine and detailed investigation of the correlations between spleen volume and all three hematological parameters, though even this report investigated up to 6 months after liver transplantation (Ohira et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…It is well known that the platelet count decreased with stage advancement of liver diseases in chronic hepatitis C patients [2,49,50,51,52]. Chronic hepatitis C is associated with variable degrees of anemia, neutropenia, and/or thrombocytopenia [52].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, preoperative PLT was only one factor significantly associated with thrombocytopenia at 12 months after LDLT. Some reports also showed that severe thrombocytopenia before LT correlated with delayed recovery of PLT after LT (18, 19). In the analysis of the relationship between splenic volume and thrombocytopenia in adult patients who underwent LT, the coexistence of splenomegaly and thrombocytopenia was a predictable factor for persistent thrombocytopenia (18).…”
Section: Discussionmentioning
confidence: 99%